The Relationship between Organizational Entrepreneurship and Communications Network in Health Deputy of Ahvaz University of Medical Sciences - Rahim Khodayari-Zarnaq; Hamid Ravaghi; Nayeb Fadayi; Arman Sanadgol; Khorshid Mobasseri (Kerman University of Medical Sciences, 2017)
Background & Objectives: Effective communication can be considered as the foundation of modern organizations and effective organizational communication can provide an appropriate context for organizational entrepreneurship. This study investigated the relationship between organizational communications network and organizational entrepreneurship in ViceChancellor for Health Affairs in Ahvaz University of Medical Sciences. Methods: This descriptive-analytical and cross-sectional study was conducted in 2015. Statistical population of the research was all staff of Vice-Chancellor for Health Affairs in Ahvaz University of Medical Sciences (n=106), of whom, 90 ones returned their questionnaires. Data gathering was done using the questionnaire of organizational communication network including 14 questions and the questionnaire for organizational entrepreneurship including 31 questions. Scoring was done using 5-item Likert scale. Data analysis was performed through SPSS16 and using t-test, ANOVA and correlation coefficient. Results: Mean score of communication network was 3.28 and mean score of organizational entrepreneurship was 3.13. The results showed a significant direct relationship between organizational communications network and entrepreneurship (P <0.001). Conclusion: According to the results of the present study, having an efficient communications network in organization makes the organization potentially entrepreneur. Therefore, organizations should try to create friendly and collaborative relationships among all staff through holding educational programs. Keywords: Organization, Communications network, Organizational entrepreneurship, Health Vice-chancellor Citation: Khodayari-Zarnaq R, Ravaghi H, Fadayi Dehcheshme N, Sanadgol A, Mobasseri K. The Relationship between Organizational Entrepreneurship and Communications Network in Health Deputy of Ahvaz University of Medical Sciences. Journal of Health Based Research 2017; 3(1): 39-49.